2019
DOI: 10.1002/aorn.12841
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Environmental and Physical Ergonomic Conditions of ORs in Turkey

Abstract: This descriptive, cross-sectional study in hospital ORs in İzmir, Turkey, assessed the environmental and physical ergonomic conditions that may place perioperative personnel at risk for injury or illness. We used an ergonomic conditions and risk factor description form to collect data in 58 ORs in nine different hospitals. We identified that the noise level and general air quality in the ORs were within recommended levels. However, none of the ORs had a surgical smoke evacuation system, pressure-absorbing mats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
(22 reference statements)
0
11
0
Order By: Relevance
“…Similar to this finding, many studies have found that noise levels during surgery exceed the WHO recommendation. In the study conducted by Yasak and Vural 21 in Turkey, the mean noise level during surgery was 54.29 dB(A). Keller et al 5 found that the mean noise levels in three phases of surgery were as follows: 54.52 ± 1.55, 55.84 ± 1.73, and 56.34 ± 1.93 dB(A).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to this finding, many studies have found that noise levels during surgery exceed the WHO recommendation. In the study conducted by Yasak and Vural 21 in Turkey, the mean noise level during surgery was 54.29 dB(A). Keller et al 5 found that the mean noise levels in three phases of surgery were as follows: 54.52 ± 1.55, 55.84 ± 1.73, and 56.34 ± 1.93 dB(A).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers used a variety of data collection methods, including survey, 15,16,20,23,24,25 survey with a physical examination, 26 survey with an observation, 17-19 survey with an observation and a skills checklist, 22 survey with observations and interviews, 21 and observations 27 …”
Section: Review Of the Literaturementioning
confidence: 99%
“…Some recent literature addressed the ergonomic risks that surgeons face in the OR, 23,28,29 and multiple studies included perioperative personnel 16‐22,24‐27 . However, few of the studies we reviewed focused on perioperative nurses, 17,18,22 and one study conducted in the Netherlands focused on operating assistants— non‐nurse team members who functioned in the circulator, scrub person, and first assistant roles 20 .…”
Section: Review Of the Literaturementioning
confidence: 99%
See 2 more Smart Citations